Emily Brontë's Wuthering Heights [videorecording (DVD)] - Sakamoto, Ryūichi, 1952-2023 (Paramount Pictures, 2022)
Shot on location in Yorkshire, this is the first screen adaptation to present Brontë's complete story of two generations of the Earnshaw and Linton families, as their lives and fortunes intertwine in a complex web dominated by the passionate relationship between doomed lovers Heathcliff (Ralph Fiennes) and Cathy (Juliette Binoche).